AN EVALUATIVE STUDY ON THE IMPACT OF RAJASTHAN JANANI SHISHU SURAKSHA YOJANA SCHEME IN IMPROVING MATERNAL AND CHILD HEALTH OUTCOMES IN RAJASTHAN (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2023)
The Rajasthan Janani Shishu Suraksha Yojana (JSSY) has played a pivotal role in promoting maternal and child health in Rajasthan, India. This paper aims to assess the effectiveness of the JSSY initiative in improving health outcomes for mothers and children in the state. The study evaluates the program's impact on hospital deliveries, neonatal mortality rates, and access to maternal and child healthcare services. It also examines the challenges and obstacles faced in the implementation of the JSSY scheme. The research findings are expected to contribute to evidence-based policymaking and the enhancement of healthcare for mothers and children, not only in Rajasthan but also in other regions facing similar healthcare challenges.